2017
DOI: 10.1016/j.pbb.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

High Drinking in the Dark (HDID) mice are sensitive to the effects of some clinically relevant drugs to reduce binge-like drinking

Abstract: Background There is a serious public health need for better understanding of alcohol use disorder disease mechanisms and for improved treatments. At this writing, only three drugs are approved by the Food and Drug Administration as medications to treat alcohol use disorders – disulfiram, naltrexone, and acamprosate. Binge drinking is a form of abusive alcohol drinking defined by the NIAAA as a drinking to blood alcohol levels (BALs) > 0.08% during a period of approximately 2 hr. To model genetic risk for binge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 51 publications
(69 reference statements)
6
31
0
Order By: Relevance
“…In the “DID” studies, systemic administration of doses of R(+)-baclofen in the 5–10 mg/kg range markedly reduced alcohol intake in C57BL/6J mice ( 18 , 25 ), selectively bred High Alcohol Preferring 1 (HAP1) mice ( 18 ), and High DID (HDID) mice (selectively bred for high alcohol drinking under the DID regimen) ( 26 ). When tested in the SHAC procedure, baclofen (2.5 and 5 mg/kg, i.p.)…”
Section: Baclofen Effect On Alcohol Drinkingmentioning
confidence: 99%
“…In the “DID” studies, systemic administration of doses of R(+)-baclofen in the 5–10 mg/kg range markedly reduced alcohol intake in C57BL/6J mice ( 18 , 25 ), selectively bred High Alcohol Preferring 1 (HAP1) mice ( 18 ), and High DID (HDID) mice (selectively bred for high alcohol drinking under the DID regimen) ( 26 ). When tested in the SHAC procedure, baclofen (2.5 and 5 mg/kg, i.p.)…”
Section: Baclofen Effect On Alcohol Drinkingmentioning
confidence: 99%
“…With B6 mice and a dose range of 2-8 mg/kg, previous data have shown that NTX can reduce EtOH binge-like intake using the DID model, although some sex differences have been reported (Kamdar et al, 2007;Tarragón et al, 2012;Zhou et al, 2019;Navarro et al, 2019). It is important to mention, however, that doses of NTX as high as 10 mg/kg have failed to reduce EtOH intake in mice selected for high blood EtOH levels (HDID lines) obtained using the DID model (Crabbe et al, 2017). HDID lines show remarkably high EtOH intakes (Crabbe et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Starting with a genetically heterogeneous progenitor stock (HS/NPT), selective breeding was carried out to create 2 unique High Drinking in the Dark (HDID‐1, HDID‐2) mouse lines that represent models of genetic risk for binge‐like drinking (Crabbe et al, ; Crabbe et al, ). HDID and HS/NPT mice have been extensively characterized (Barkley‐Levenson and Crabbe, ; Barkley‐Levenson and Crabbe, ; Barkley‐Levenson and Crabbe, ; Barkley‐Levenson and Crabbe, ; Barkley‐Levenson et al, ; Barkley‐Levenson et al, ; Crabbe et al, ; Crabbe et al, ; Crabbe et al, ; Crabbe et al, ; Crabbe et al, ; Crabbe et al, ; Crabbe et al, ; Ferguson et al, ; Ferguson et al, ; Fritz et al, ; Iancu et al, ; Iancu et al, ; Metten et al, ). Of particular relevance to the current studies are the findings that HDID mice exhibit behavioral impairment after DID (Crabbe et al, ), withdrawal after a single binge‐drinking session (Crabbe et al, ), and do not exhibit altered preference for saccharin or avoidance of quinine solutions (Crabbe et al, ) or alcohol clearance rates (Crabbe et al, ).…”
mentioning
confidence: 99%
“…We have recently focused on attempting to reduce binge‐like drinking pharmacologically in HDID mice. We first tested whether drugs of known clinical relevance could modulate binge‐like EtOH drinking in HDID mice and found that HDID mice were sensitive to the effects of acamprosate and baclofen, but not naltrexone (Crabbe et al, ). These findings suggested that genetic differences between HDID and C57BL/6 mice may result in different responses to therapeutic compounds.…”
mentioning
confidence: 99%